PENENTUAN MINAT SISWA MENGGUNAKAN METODE PROFILE MATCHING - Azwar Azwar; Fitri Nasir Masi (Celebes Computer Science Journal, 2020)
Public High School one Paguyaman has implemented curriculum 2013, interest at the high school level is done early, namely from the beginning of entry in grade X. Interest at the high school level is divided into 3 interests namely MIPA, IPS and Bahasa. However, in the process of interest found there are still many students who choose interests incompatible with their competencies. This research aims to implement the Profile Matching method on the development of the system to support student interest selection decisions. The technique used is Research and Development. Based on the results of the research that has been done, it is known that the Mathcing Profile method can be implanted. This is evidenced by the results of tests conducted by white box testing method and Black Box testing.